Heart enhancers with deeply conserved regulatory activity are established early in zebrafish development. Issue 1 (December 2018) - Yuan, Xuefei; Song, Mengyi; Devine, Patrick; Bruneau, Benoit; Scott, Ian; Wilson, Michael
Abstract During the phylotypic period, embryos from different genera show similar gene expression patterns, implying common regulatory mechanisms. Here we set out to identify enhancers involved in the initial events of cardiogenesis, which occurs during the phylotypic period. We isolate early cardiac progenitor cells from zebrafish embryos and characterize 3838 open chromatin regions specific to this cell population. Of these regions, 162 overlap with conserved non-coding elements (CNEs) that also map to open chromatin regions in human. Most of the zebrafish conserved open chromatin elements tested drive gene expression in the developing heart. Despite modest sequence identity, human orthologous open chromatin regions recapitulate the spatial temporal expression patterns of the zebrafish sequence, potentially providing a basis for phylotypic gene expression patterns. Genome-wide, we discover 5598 zebrafish-human conserved open chromatin regions, suggesting that a diverse repertoire of ancient enhancers is established prior to organogenesis and the phylotypic period. During early embryogenesis, critical cardiac specification events occur. Here the authors isolate cardiac progenitor cells from early zebrafish embryos and characterize accessible chromatin regions specific to this cell population, finding that many of these regions overlap with conserved non-coding elements that are ortholgous to accessible chromatin regions in human.